Shale gas as an alternative energy source - Padmanabhan, E. (IGI Global, 2018)
Shale gas has been considered as an unconventional resource to date due to economics and technical challenges encountered. Under current circumstances, shale gas has and is receiving increasing attention as it is being quickly known as a viable energy resource. Countries who have been out of the energy game so far have an opportunity to be key players in the same industry. Current enhancement in technology and improved methods for fracking have proven that recovering shale gas is a viable and economically sound option in this century. Â© 2018, IGI Global. All rights reserved.